2006
DOI: 10.1111/j.1944-9720.2006.tb02280.x
|View full text |Cite
|
Sign up to set email alerts
|

Exercices de style: Developing Multiple Competencies Through a Writing Portfolio

Abstract: This article presents a writing portfolio project whose primary goal is to integrate the development of projiciency skills, content knowledge, and grammatical competence through literary study. Excerpts from Queneau's (1947) Exercices de style, which tells the same story 99 times, serve as the basis for this portfolio project: These excerpts are both the input for grammar instruction and the model for student writing. Students prepare multiple drafts of their written texts according to a process‐oriented appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 24 publications
2
33
0
Order By: Relevance
“…This article, then, addresses a particularly important but surprisingly neglected area of L2 writing: actual instructional practices, which, as Leki, Cumming, and Silva (2008) note, 'has been a perplexingly overlooked and underreported aspect of research' (p. 81). While some work within FL does provide descriptions of classroom activities and their outcomes, virtually all of these works focus on writing in the more-commonly-taught languages of French (Krug, 2004;Paesani, 2006), Spanish (Armstrong & Retterer, 2008;Pérez-Sotelo & González-Bueno, 2003), and German (Becker, 2003;Byrnes, 2002;High, Hoyer, & Wakefield, 2002). Some genre-based instructional frameworks for the teaching of second language writing have also been provided in the literature (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…This article, then, addresses a particularly important but surprisingly neglected area of L2 writing: actual instructional practices, which, as Leki, Cumming, and Silva (2008) note, 'has been a perplexingly overlooked and underreported aspect of research' (p. 81). While some work within FL does provide descriptions of classroom activities and their outcomes, virtually all of these works focus on writing in the more-commonly-taught languages of French (Krug, 2004;Paesani, 2006), Spanish (Armstrong & Retterer, 2008;Pérez-Sotelo & González-Bueno, 2003), and German (Becker, 2003;Byrnes, 2002;High, Hoyer, & Wakefield, 2002). Some genre-based instructional frameworks for the teaching of second language writing have also been provided in the literature (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…To the best of these researchers' knowledge, Bataineh, Al-Karasneh, Al-Barakat and Bataineh (2007) and Alnethami (2009) most probably constitute the only local research contributions to portfoliobased instruction and assessment. As regards writing competences, however, literature from around the world (e.g., Apple & Shimo, 2004;Caner, 2010;Fahim & Jalili, 2013;Hamp-Lyons & Condon, 2000;Hirvela & Sweetland, 2005;Khodadady & Khodabakhshzade, 2012;Marefat, 2004;Nezakatgoo, 2011;Paesani, 2006) provides empirical evidence that portfolio assessment does significantly contribute to the improvement of learners' writing performance. In addition, even though a few studies address the potential benefits of portfolio assessment in the EFL writing classroom (e.g., Fahim & Jalili, 2013;Hamp-Lyons & Condon, 2000;Khodadady & Khodabakhshzade, 2012;Marefat, 2004), most of the literature on portfolio assessment targets writing in first language contexts (Hamp-Lyons & Condon, 2000;Hirvela & Pierson, 2000;Hirvela & Sweetland, 2005;Weigle, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Three of these studies (Paesani, 2006;Plummer and Busse, 2006;Yañez Prieto, 2010) reported improvements in writing proficiency, while Timucin (2001) reported changes in reading comprehension skills. Paesani (2006) focused on a writing portfolio project in an advanced grammar and stylistics course in a university FFL context. Based on a mixed-methods analysis of writing portfolios, Paesani concluded The use of a process-based methodology focused on stylistics to teach metadiscursive function in fiction Stylistics is effective for text-based interpretations of literature; this method is also useful for raising language awareness and as a framework for class discussions beyond stylistics content; stylistics can also be effective with less proficient L2 learners (facilitates L2 learning and increases learner motivation)…”
Section: Studies Indicating Improved L2 Performancementioning
confidence: 94%
“…Timucin (2001) University EFL 2 Investigation and reflection of learners' responses to an integrated languagebased and stylistics approach to teaching literature Integrated teaching approach increased levels of student involvement and positively informed the classroom teaching and learning dynamic; learners in the experimental group improved their reading comprehension skills Turkey Paesani (2006) University FFL 3 Examining the benefits of a writing portfolio to improve learners' L2 proficiency skills in grammar and stylistics The value of the writing portfolio in achieving its goal is 'overwhelmingly positive'; learners' improved L2 proficiency and improved understanding of literary texts NR 4 Plummer and Busse (2006) University EFL Examining the role of e-learning and stylistics in English studies in a German context, the logistics of implementing an appropriate course and learners' responses to, and performances on, the course E-learning may be best in a blended form, and most learners preferred a blended learning model; stylistics may help develop transferable analytic skills; learners' writing improved Germany Al-Jarf (2007) University EFL Learners' ability to comprehend and analyze advertisements and identify their stylistic features As understanding advertisements is a developmental process, it should be taught accordingly (stylistics is identified as a necessary element in the teaching schedule)…”
Section: Ukmentioning
confidence: 99%